Atomic environments : nuclear technologies, the natural world, and policymaking, 1945-1960 - Oatsvall, Neil S., 1982- (Tuscaloosa : The University of Alabama Press, 2023)
"Demonstrates how policymakers influenced environmental science during the early nuclear age In Atomic Environments: Nuclear Technologies, the Natural World, and Policymaking, 1945-1960, Neil S. Oatsvall examines how top officials in the Truman and Eisenhower administrations used environmental science to develop nuclear strategy at the beginning of the Cold War. While many people were involved in research and analysis during the period in question, it was at highest levels of executive decision-making where environmental science and nuclear science most clearly combined to shape the nation's policies. Oatsvall clearly demonstrates how the natural world and the scientific disciplines that study it became integral parts of nuclear science rather than adversarial fields of knowledge. But while nuclear technologies heavily depended on environmental science to develop, those same technologies frequently caused great harm to the natural world. Moreover, while some individuals expressed real anxieties about the damage wrought by nuclear technologies, policymakers as a class consistently made choices that privileged nuclear boosterism and secrecy, prioritizing institutional values over the lives and living systems that they were ostensibly charged to protect. By scrutinizing institutional policymaking practices and agendas at the birth of the nuclear age, a constant set of values becomes clear. Oatsvall reveals an emerging technocratic class that routinely valued knowledge about the environment to help create and maintain a nuclear arsenal, despite its existential threat to life on earth and the negative effects many nuclear technologies had on ecosystems and the American people alike. Although policymakers took their charge to protect and advance the welfare of the United States and its people seriously, Atomic Environments demonstrates how they often failed to do so because their allegiance to the US nuclear hierarchy blinded them to the real risks and dangers of the nuclear age. "--
"In "Atomic Environments," Neil S. Oatsvall examines how top policymakers in the Truman and Eisenhower administrations used environmental science in their work developing nuclear strategy at the beginning of the Cold War. While many people were involved in research and analysis during the period in question, it was at highest levels of executive decision-making where environmental science and nuclear science most clearly combined to shape the nation's policies. Because making and testing weapons, dealing with fallout and nuclear waste, and finding uses for radioactive byproducts required advanced understanding of how nuclear systems interacted with the world, policymakers utilized existing networks of environmental scientists-particularly meteorologists, geologists, and ecologists-to understand and control the United States' use of nuclear technology. Instead of profiling individuals, Oatsvall focuses on executive institutions, especially the leadership of the Atomic Energy Commission (AEC) and high level officials in the Truman and Eisenhower White Houses, including the presidents, themselves. By scrutinizing institutional policymaking practices and agendas at the birth of the nuclear age, a constant set of values becomes clear: "Atomic Environments" reveals an emerging technocratic class that consistently valued knowledge about the environment to help create and maintain a nuclear arsenal, despite its existential threat to life on earth and the negative effects many nuclear technologies directly had on ecosystems and the American people, alike. "Atomic Environments" is divided into five chapters, each of which probes a different facet of the entanglement between environment, nuclear technologies, and policymaking. The first three chapters form a rough narrative arc about nuclear weapons. Chapter One situates bombs in their "natural habitat" by considering why nuclear tests occurred where they did and what testers thought they revealed about the natural environment and how they influenced it. Focusing on nuclear fallout, Chapter Two argues that nuclear tests actually functioned as a massive, uncontrolled experiment in world environments and human bodies that intermingled medicine, nuclear science, and environmental science. Chapter Three shows how the environmental knowledge gained in the first two chapters led to nuclear test ban treaty talks during the Eisenhower era, when the advancement of environmental knowledge and the natural world itself became crucial grounds of contention in the creation of nuclear test detection and evasion systems. The last two chapters step away from weapons to question how other nuclear technologies and facets of the U.S. nuclear program interacted with the natural world. Chapter Four examines agriculture's place in the U.S. nuclear program, from breakthrough advances in agricultural science including the use of radioisotopes and the direct application of radiation to food, to "atomic agriculture's" public relations value as a peaceful proxy, which shifted the moral calculus and further leveraged the U.S. government's atomic power. Chapter Five shows how knowledge of the natural world and the functioning of its systems proved important to uncovering the most effective ways to dispose of nuclear waste. Running throughout, Oatsvall consistently demonstrates how the natural world and the scientific disciplines that study it became integral parts of nuclear science, rather than adversarial fields of knowledge. But while nuclear technologies heavily depended on environmental science to develop, those same technologies frequently caused great harm to the natural world. Moreover, while some individuals expressed real anxieties about the damage wrought by nuclear technologies, policymakers as a class consistently made choices that privileged nuclear boosterism and secrecy, prioritizing institutional values over the lives and living systems that agencies like the AEC were ostensibly charged to protect. In the end, Oatsvall argues that although policymakers took their charge to protect and advance the welfare of the United States and its people seriously, they often failed to do so because their allegiance to the U.S. nuclear hierarchy blinded them to the real risks and dangers of the nuclear age"--
Part I. Nuclear weapons testing in Natural and Political Systems -- Bombs in Their Natural Habitats -- Fallout over Fallout -- Cold War Environmental Diplomacy -- Part II. Nuclear Technologies by Land and by Sea -- Atomic Agriculture -- From Affluence to Effluence -- Conclusion: On Nuclear Technologies, Decision Making, and Environmentalism.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 23, 2023).
eBooks on EBSCOhost
Keywords: Nuclear energy -- Government policy -- United States -- History -- 20th century; Nuclear weapons -- United States -- Testing -- History -- 20th century; Nuclear energy -- Environmental aspects -- United States -- History -- 20th century; Nuclear energy -- Research -- United States -- History -- 20th century; Énergie nucléaire -- Politique gouvernementale -- États-Unis -- Histoire -- 20e siècle.; Énergie nucléaire -- Aspect de l'environnement -- États-Unis -- Histoire -- 20e siècle.; Énergie nucléaire -- Recherche -- États-Unis -- Histoire -- 20e siècle.; HISTORY / United States / 20th Century; SCIENCE / History; Nuclear weapons -- Testing; Nuclear energy -- Research; Nuclear energy -- Government policy; Nuclear energy -- Environmental aspects; United States; 1900-1999; Electronic books; History